2022
DOI: 10.1021/acsaelm.2c00321
|View full text |Cite
|
Sign up to set email alerts
|

Role of Solvents in the Preparation of Methylammonium Bismuth Iodide (MBI) Perovskite Films for Self-Biased Photodetector Applications

Abstract: Pb-free metal halide perovskites are excellent light-harvesting materials for photodetector applications because of their inherent remarkable optoelectronic properties with lower-temperature processability. However, to date, the realization of device-quality Pb-free metal halide films is still a great challenge. Here, using a single-step spin coating method, we have synthesized Pb-free methylammonium bismuth iodide [(CH3NH3)3Bi2I9 (MBI)] perovskite films using different solvents, such as γ-butyrolactone (GBL),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In MABiI, the (00l) planes dominate the XRD spectrum, while (h0l) peaks are also significant in S.MABiI, indicating a less oriented polycrystalline structure than the undoped compound. Raman spectroscopy (Figure b) confirms that the [Bi 2 I 9 ] 3– octahedra are bonded to the CH 3 NH 3 + cations. ,, The peak at 116 cm –1 in the MABiI spectrum shifts to 120 cm –1 in S.MABiI, where a peak arises at 108 cm –1 . This has previously been reported in sulfur-doped MABiI samples, and it is related to the sulfur inclusion in the structure.…”
Section: Results and Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In MABiI, the (00l) planes dominate the XRD spectrum, while (h0l) peaks are also significant in S.MABiI, indicating a less oriented polycrystalline structure than the undoped compound. Raman spectroscopy (Figure b) confirms that the [Bi 2 I 9 ] 3– octahedra are bonded to the CH 3 NH 3 + cations. ,, The peak at 116 cm –1 in the MABiI spectrum shifts to 120 cm –1 in S.MABiI, where a peak arises at 108 cm –1 . This has previously been reported in sulfur-doped MABiI samples, and it is related to the sulfur inclusion in the structure.…”
Section: Results and Discussionmentioning
confidence: 71%
“…The crystal structure of S.MABiI and MABiI films, produced by drop-casting, showed hexagonal symmetry belonging to the P 6 3 / mmc space group, as confirmed by XRD ( Figure 1 a). 25 , 27 31 The main diffraction plain is (006) in both samples. In MABiI, the (00l) planes dominate the XRD spectrum, while (h0l) peaks are also significant in S.MABiI, indicating a less oriented polycrystalline structure than the undoped compound.…”
Section: Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At present, due to the superior optoelectronic properties, MA 3 Bi 2 I 9 has received extensive research attention in the field of semiconductor detectors and fruitful results have been produced. [65][66][67][68][69][70] Through the study of this work, the ultrafast decay time and superior environmental stability of MA 3 Bi 2 Br 9 also give the crystals important application prospects in the field of the ultrahigh time resolution detection of high-energy rays no matter whether through direct or indirect means. Meanwhile, the MA 3 Bi 2 (Br 0.74 I 0.26 ) 9 and MA 3 Bi 2 (Br 0.62 I 0.38 ) 9 mixed crystals exhibit excellent balance among the good absorption properties, suitable luminescence bands and good environmental stability, which are also valuable for obtaining photodetectors with balanced performances.…”
Section: Absorption Characteristics Of Ma 3 Bi 2 Xmentioning
confidence: 99%
“… 38 Moreover, Shah et al revealed that 2-methoxyethanol is the best solvent choice for the best coverage, smallest grain size, good optical properties, and better photo-response of the MA 3 Bi 2 I 9 perovskite thin film-based photodetector. 49 Mixed halides (Cl/I) of MA 3 Bi 2 I 6 Cl 3 -based photodetector have been reported to obtain photo-responsivities and specific detectivities roughly three times greater than pristine MA 3 Bi 2 I 9 -based devices. 50 In addition, one research work has also been reported with diammonium bismuth perovskites.…”
Section: Introductionmentioning
confidence: 99%